Incidence and Risk Factors of Congenital Heart Diseases in Syndromic Neonates - Rahman, Md Mahbubur; Al Amin, Abdullah; Ferdaus, Jannatul; Quader, Mohammad Abdul (Community Based Medical Journal, 2023)
Congenital heart defects (CHD) are the most common types of major birth defects, leading cause of infant morbidity and mortality. Syndromic babies are more affected by CHD. This observational study was conducted in a tertiary care hospital of military facility in Bangladesh. Eighty syndromic neonates were studied through history, physical examination and investigated for incidence and risk factors for CHD. Out of 80 syndromic neonates 61(76.3%) were found having CHD. Male female ratio was 1.18:1. Average age at diagnosis was 25±1.6 days of age. Down Syndrome (DS) and Congenital Rubella Syndrome (CRS) were the most common syndromes. Ventricular Septal defect (VSD) and Atrial septal defect (ASD) II were the most common CHD. Consanguinity, extracardiac malformations, maternal illness (HTN, DM, Hypothyroidism etc.), both fertility and non-fertility medication are also found to be associated with CHD in Syndromic neonates. CHDs have serious implications and it is important to understand them and how they may affect the child so that appropriate medical and surgical treatment may be provided. So, early detection of CHD in neonate will be able to decrease morbidity as well as mortality. CBMJ 2023 January: Vol. 12 No. 01 P: 17-21